Empirical or rational truffle cultivation? It is time to choose. - Chevalier, Gerard; Pargney, Jean C. (Forest Systems, 2014)
Aim of study: The aim of this study was to finalize a new method of truffle cultivation in order to obtain an earlier, more regular and sizeable production of high quality fruiting bodies. Area of study: The experimentation was carried out in France (country of Dordogne, south-western France) and Italy (country of Marches, eastern central Italy) for more than one decade. Material and methods: For the first time the method is based on scientific data on truffle biology particularly: the dynamic system of mycorrhization by the truffle and by other fungi; the saprophytic capability of the truffle; the ability of its mycelium for decomposing certain minerals and organic materials in the “brûlés”. The basic principle concern the work of the soil and the upkeep of the root system: to work the soil immediately after the plantation of mycorrhizal seedlings, deeply enough, with adapted tools, in order to do not compact the soil, aerate it, favour the production of deep fruiting bodies not exposed to high temperatures, dryness, frost, parasites… ; cut accurately the roots in order to regenerate them and consequently to provide food for the truffle mycelium. Main results: The result has been a new cultivation method designated “differentiated” and called “MRT”, with adapted work of the soil on the lines of plantation and upkeep of the grass between them, to maintain the cohabitation between areas where the mycelium is present, from those where it is absent. Research highlights: Research is going on to improve the techniques and particularly finalize tools more precise and more adapted for working the soil and maintaining the root system in a best way. Keywords: truffle; production; nutrition; soil, root system; cultivation tools.